Cocoa biotechnology status, constraint, and future prospect in Malaysia: a review / Amirul Izwan Sahari - Sahari, Amirul Izwan (Faculty of Plantation and Agrotechnology, 2019)
Theobroma cacao is one of the world’s most valuable crops and used to be one of the biggest commodities in Malaysia back in the 1950s till 1990s. The current status, constraint and future prospect must be further studied. A review was carried out to observe the status of cocoa and to identify the constraint of cocoa biotechnology in Malaysia. Good varieties of cocoa that can produce high yield and can withstand the changing weather. However, yield started to decline because of diseases, pests and environmental stress. Poor bean quality also caused by pre-harvest and post-harvest process. The uncertainty of transgenic cocoa make consumer doubted the effect of transgenic crop when consumed. Low number of new cocoa genetics because not many research conducted and long juvenile period of cocoa make it hard to observe the outcome of in vitro somatic embryogenesis. Suitable strategies can be used by farmers to choose the right varieties to be planted in the field. The involvement of plant biotechnology related-company is recommended to increase the chances to obtain new cocoa varieties. Financial support from local government and implementation of modern molecular tools in cocoa biotechnology research will undoubtedly bring new cocoa varieties for commercial use.